Transient Coupled Flow Model for Matrix-Fracture in High-Pressure Gas Reservoirs Opened by Gas Drilling. (10th February 2023) - Liu, Jiajie; Li, Gao; Ye, Zhi; He, Wang; Zeng, Zhihao
Abstract : Gas drilling technology is an effective method to protect low permeability tight sandstone reservoirs from damage. However, using this technology to drill high-pressure fractured reservoirs, the fluid flow characteristics are extremely complex, leading to drilling safety challenges. Therefore, based on the conservation equations of mass, momentum, and energy, a new transient coupled flow model in matrix-fracture is established for high-pressure gas reservoirs opened by gas drilling, considering convection term and energy equation, to research the pressure and flow velocity transient behaviors. This model is solved by Shaher Momani's algorithm and CyabJiBe format, and the type curves of the pressure and flow velocity are plotted. The three flow stages are developed, and the impact of parameters and equation terms on the transient flow behavior is analyzed and discussed, such as the energy equation, the matrix permeability (k ), the fracture aperture (L f ), and the fracture outlet pressure. It is found that the energy equation term of the model has a great influence on the transient characteristics such as velocity and pressure, which cannot be ignored. In the first flow stage, the flow velocity characteristics are not affected by the matrix parameters being extremely unstable, but in the second and third stages, the influence of the gas supplied to fracture cannot be ignored. The proposed transient coupled flow model provides a new understanding of the transient flow behavior in matrix-fracture for high-pressure reservoirs during gas drilling, which can be used to interpret the characteristics of pressure and velocity more realistically, to provide support for safe drilling of gas drilling.